2022
DOI: 10.1002/er.7992
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanostructured bismuth‐cobalt oxides/hydroxides binder‐free electrodes fabricated by two‐step electrodeposition for high‐performance supercapacitors

Abstract: Herein, a two-step electrodeposition technique is adopted for the binder-free fabrication of nanostructured bilayered active material electrodes to achieve a high-performance supercapacitor with reducing charge-transfer resistance. Hybridnanostructured bismuth-cobalt oxides/hydroxides electrode (Bi 2 O 3 @Co(OH) 2 ) active materials are successfully grown on a 3D nickel foam substrate via versatile electrodeposition. Nanostructured Co(OH) 2 is deposited on Bi 2 O 3 coated nickel foams using different electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…[179] A bimetallic hybrid Bi 2 O 3 @Co(OH) 2 /Ni foam nanostructure-based composite binder-free electrode is fabricated using the electrodeposition technique is successfully reported by Nguyen et al. [180] Fabrication of SC devices that can withstand a high-temperature condition is extremely crucial for powering such applications that work under hightemperature conditions. Therefore, the safety of SCs as well as high efficiency is the foremost requirement.…”
Section: Cobalt Oxides and Composites As Binder-free Sc Electrodesmentioning
confidence: 99%
“…[179] A bimetallic hybrid Bi 2 O 3 @Co(OH) 2 /Ni foam nanostructure-based composite binder-free electrode is fabricated using the electrodeposition technique is successfully reported by Nguyen et al. [180] Fabrication of SC devices that can withstand a high-temperature condition is extremely crucial for powering such applications that work under hightemperature conditions. Therefore, the safety of SCs as well as high efficiency is the foremost requirement.…”
Section: Cobalt Oxides and Composites As Binder-free Sc Electrodesmentioning
confidence: 99%
“…Extensive research on nanostructured materials and their characterization have shown their uniqueness and advantages for applications in various fields of science and engineering including chemistry, physics, biology, biotechnology, and medicine. Typical applications are related to electrochemical energy conversion and storage [ 100 , 107 , 108 ], including lithium-based batteries [ 109 ], supercapacitors [ 99 , 110 ], and fuel cells [ 111 ]. Energy-related applications of nanostructured materials cover also electrochromic energy storage systems [ 112 ], solar cells, and photovoltaics [ 113 ] as well as thermoelectric systems and devices [ 114 ].…”
Section: Introductionmentioning
confidence: 99%